Effective Leadership: From The Perspective of Trait Theory and Behavior Theory - Dian Marlina Verawati; Budi Hartono (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
Leadership is an interesting and important topic to be discussed for all time. It is related to the important role of leaders in an organization or group of people. Whether or not the condition of the organization or group in the future depends on the role of the leader at this time. A leader is expected to have professional technical and managerial skills. The technical skills are under their fields, while managerial skills require their role in leading others. These skills are reflected in his actions, such as selecting, educating, motivating, developing up to terminating employment relations. Leadership and adjusting to change are the biggest challenges facing leaders today. Leaders must use leadership styles that are most effective in influencing subordinates' perceptions about the goals to be achieved and ways to achieve them. There are three leadership theories, namely, traits theory, behavior theory, and contingency theory. All three theories have different basic assumptions. This article only focuses on the theory of traits theory and behavior theory. Trait theory believes that leaders are born with several inherent characteristics such as courage, intelligence, strength, initiative, responsibility. In contrast to trait theory, behavior theory believes that leaders can be formed with education and training, where leadership functions such as planning, organizing, directing, controlling are more prominent than the leader's character.